High Inflation, Price Stability and Histeresys Effect: Evidence from Argentina - Dabús, Carlos Darío (2016)
We estimate a Currency Substitution model for 1980-2013 periods in Argentina. Following the Mongardini and Mueller (2000) specification, our paper studies the persistence of lower demand of local money, or dollarization, by including a hysteresis variable. By applying an ARDL (Auto Regressive Distributed Lags) model, we found a clear ratchet effect, which implies that in the short run agents do not adjust to changes on the fundamentals, leading to a significant hysteresis variable.